2002
DOI: 10.1007/s00405-001-0422-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect on arterial blood gases and heart rate of bilateral nasal packing

Abstract: In order to elucidate the blood gas and heart rate changes caused by bilateral nasal packing, 21 healthy subjects who had had septoplasty or septorhinoplasty were investigated with pre- and post-operative blood gas measurements and 24-h Holter monitoring. Nasal packing caused a significant decrease in O2 saturation (P < 0.05), a borderline decrease in PO2 (P = 0.09), insignificant changes in PCO2, pH and HCO3 (P > 0.05), a significant increase in minimum and mean heart rates (P < 0.05) and insignificant change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
4
16
0
4
Order By: Relevance
“…14 Studies in human beings were carried out by measuring arterial blood gases and the hypoxemia was noted in patients of septoplasty followed by nasal packing. 15,16 Similar results were also obtained in blood oxygen saturation (SpO 2 ) using pulse oximetry in patients with adenotonsillectomy and septoplasty followed by nasal packing. 17 However, contrary results are also reported in literature.…”
Section: Discussionsupporting
confidence: 54%
“…14 Studies in human beings were carried out by measuring arterial blood gases and the hypoxemia was noted in patients of septoplasty followed by nasal packing. 15,16 Similar results were also obtained in blood oxygen saturation (SpO 2 ) using pulse oximetry in patients with adenotonsillectomy and septoplasty followed by nasal packing. 17 However, contrary results are also reported in literature.…”
Section: Discussionsupporting
confidence: 54%
“…As mouth is the only airway for a patient with nasal packs, improper swallowing of oral secretions might also cause breathing diYculty. The use of nasal packs without airways can cause a decrease in oxygen saturation and partial oxygen pressure, especially in patients with obstructive sleep apnea syndrome [12][13][14]. Regli et al suggested that all patients with nasal packs should receive postoperative oxygen supplementation in order to prevent the increase in apnea-hypopnea and oxygen desaturation indices [15].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies performed using bilateral nasal packing after nasal operations, the nasal obstruction caused a significant decrease in blood O 2 saturation [15]. However, mechanical stimulation of the nasal mucosa may have introduced a bias in these studies.…”
Section: Discussionmentioning
confidence: 99%